Effect of planting technique and amendment type on pearl millet yield, nutrient uptake, and water use on degraded land in Niger - Fatondji, D.; Martius, C.; Bielders, Charles L.; Vlek, Paul L.G.; Bationo, B. André; Gerard, Bruno G. (Springer, 2007)
Due to increased population pressure and limited availability of fertile land, farmers on desert fringes increasingly rely on marginal land for agricultural production, which they have learned to rehabilitate with different technologies for soils and water conservation. One such method is the indigenous zai technique used in the Sahel. It combines water harvesting and targeted application of organic amendments by the use of small pits dug into the hardened soil. To study the resource use efficiency of this technique, experiments were conducted 1999–2000, on-station at ICRISAT in Niger, and on-farm at two locations on degraded lands. On-station, the effect of application rate of millet straw and cattle manure on millet dry matter production was studied. On-farm, the effects of organic amendment type (millet straw and cattle manure, at the rate of 300 g per plant) and water harvesting (with and without water harvesting) on millet grain yield, dry matter production, and water use were studied. First, the comparison of zai vs. flat planting, both unamended, resulted in a 3- to 4-fold (in one case, even 19-fold) increase in grain yield on-farm in both years, which points to the yield effects of improved water harvesting in the zai alone. Zai improved the water use efficiency by a factor of about 2. The yields increased further with the application of organic amendments. Manure resulted in 2–68 times better grain yields than no amendment and 2–7 times better grain yields than millet straw (higher on the more degraded soils). Millet dry matter produced per unit of manure N or K was higher than that of millet straw, a tendency that was similar for all rates of application. Zai improved nutrient uptake in the range of 43–64% for N, 50–87% for P and 58–66% for K. Zai increased grain yield produced per unit N (8 vs. 5 kg kg?1) and K (10 vs. 6 kg kg?1) compared to flat; so is the effect of cattle manure compared to millet straw (9 vs. 4 kg kg?1, and 14 vs. 3 kg kg?1), respectively, Therefore zai shows a good potential for increasing agronomic efficiency and nutrient use efficiency. Increasing the rate of cattle manure application from 1 to 3 t ha?1 increased the yield by 115% TDM, but increasing the manure application rate further from 3 to 5 t ha?1 only gave an additional 12% yield increase, which shows that optimum application rates are around 3t ha?1.